The life of the traditional population of the Xikrin ethnic group in the face of the S11D project and the understanding of the inter-american court of human rights - Bentes , Natália Mascarenhas Simões; Arruda , Paula Regina Benassuly; Pereira , Alsidéa Lice de Carvalho Jennings; Souza, Arthur de Oliveira (Seven Editora, 2023)
Brazil is a multiethnic and pluricultural country, from the beginning of its development to its sovereign state, having as its premise, to defend and value its heritage and its ethnic and regional diversity; caring for and promoting human rights in the various collectivities. In addition, as a legal support mechanism, international provisions such as the Inter-American Convention on Human Rights, which contemplates indigenous peoples and deals with the consolidation of the right to prior consultation in order to reduce the disparities in power relations present in the neoliberal state. The advent of this convention laid the foundation for the protection of the human rights of indigenous peoples. The main objective of this research is the legal discussion of the case of the Xikrin indigenous people in relation to the S11D project of the mining company Vale, in the State of Pará which, according to the lawsuits, has promoted social and environmental impacts to their villages, thus urging the need to promote specific studies; such as the Prior Consultation to ascertain the due violations of the legal mechanisms related to the stages of environmental licensing, as well as the discussion for the creation and implementation of a joint monitoring and follow-up committee between the Xikrin and the managers of the S11D enterprise, for the inspection and elaboration of public policies that respect the human rights of the Xikrin people. DOI:https://doi.org/10.56238/interdiinovationscrese-023